2013
DOI: 10.5688/ajpe776112
|View full text |Cite
|
Sign up to set email alerts
|

A Need to Rethink and Mold Consensus Regarding Pharmacy Education in Developing Countries

Abstract: Health systems struggle to keep up with overwhelming new health challenges.1 Beside financial constraints, public expectations and technological advancement of health service, the other biggest challenge faced by healthcare systems in both the developed and developing world is the high prevalence of non-communicable diseases such as diabetes and hypertension. In the developing world in particular, health systems have responded to these challenges by placing additional demands on health workers 1 and by admonis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…In recent years, health systems in both the developed and developing world have faced the challenges of financial constraints, a high prevalence of non-communicable diseases, and an increase in problems related to pharmacotherapy and morbidity and mortality associated with drug use [ 1 , 2 ]. These changes in health care have had a great impact on the field of pharmaceutical practice and on pharmacy as a profession [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, health systems in both the developed and developing world have faced the challenges of financial constraints, a high prevalence of non-communicable diseases, and an increase in problems related to pharmacotherapy and morbidity and mortality associated with drug use [ 1 , 2 ]. These changes in health care have had a great impact on the field of pharmaceutical practice and on pharmacy as a profession [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Quite a number of participants felt that the degree change was not going to be successful because of several factors within our environment especially poor collaboration among healthcare professionals within the country and intra-disciplinary disagreement within the profession. This is a valid fear because one of the challenges facing pharmacy education in developing countries is the inharmonious working relationship between different health care professionals (Hassali et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The challenge of engaging pharmacists to embrace new pharmacy roles can be addressed at the student level through education . Unfortunately, pharmacy education in developing nations has many challenges, including isolation of pharmacy education from pharmacy practice and mismatch with surrounding population healthcare needs . As we move towards re‐examining pharmacy education and reforming education to meet current health care needs, it is important to consider the input of students .…”
Section: Introductionmentioning
confidence: 99%
“…[18] As we move towards re-examining pharmacy education and reforming education to meet current health care needs, it is important to consider the input of students. [18] A study on the development of a public health course for first-year bachelor of pharmacy students in Malaysia revealed that although the majority of students felt the provided public health course was meaningful, a large portion also found it to be less interesting than other courses. [19] Such feedback from students allowed educators to refine public health education and make it engaging and relevant to student pharmacists.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation